(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: Опухоли головного мозга составляют 1,8-2,3% от общего числа онокологических заболеваний, а частота заболеваемости первичными опухолями головного мозга достигает 14,1 на 100000 населения. Менингиомы составляют 15—20 % всех первичных опухолей головного мозга, проявляются обычно в возрасте 35—55 лет, почти в два раза чаще бывают у женщин. Менингиомы больших полушарий головного мозга составляют 47% всех менингиом головного мозга. В статье изложен случай из практики гигантскойменингиомыСильвиевой щели. Данная локализацияменингиом вызывает большой интерес в связи с трудностью оперативного вмешательства, высокого риска развития послеоперационных осложнений. Annotatsiya: Onkologikkasalliklarumumiysonining 1,8-2,3% inibosh miyao’smalaritashkiletadivauchrashdarajasi 100 000 aholiga 14,1 tagayetadi. Meningiomalar, asosan, 35-55 yoshgachabo’lganbarcha bosh miyao’smalarining 15-20% initashkilqiladivaayollardadeyarliikkibarobarko’proquchraydi. Miya yarimsharlarimeningiomalaribarchamiyameningiomalarining 47% nitashkilqiladi.. Abstract: Brain tumors account for 1.8–2.3% of the total number of oncological diseases, and the incidence rate of primary brain tumors reaches 14.1 per 100,000 population. Meningiomas account for 15–20% of all primary brain tumors, usually occurring between the ages of 35–55 years, and are almost twice as common in women. Meningiomas of the cerebral hemispheres make up 47% of all brain meningiomas. The article presents a case from the practice of the giant meningioma of Sylvian fissure. This localization of meningiomas is of great interest due to the difficulties of surgical removal, a very high risk of developing postoperative vascular complications.